An Analysis of Writing Task in English Textbook for Seventh Grade of Junior High School Based on Cognitive Domain of Revised Bloomâ€™s Taxonomy - AJR, Adiyanto Edo Nugraha; Al-Baekani, Abdul Kodir; Hakim, Putri Kamalia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Cognitive Domains are important in the instructions and questions for learning tasks in the textbook, especially for helping students improve their thinking skills. The aim of this study was to analyze the cognitive process and knowledge dimension of Bloomâ€™s Revised Taxonomy represented in the writing tasks provided in the â€œEnglish for Nusantaraâ€ for seventh-grade students. This research was content analysis. This study used a checklist instrument. The research revealed that writing tasks in the textbook covered five of six categories of the cognitive process of revised Bloomâ€™s Taxonomy. The most used level of cognitive process was the remembering level. In terms of Knowledge Dimension, all Knowledge Dimensions existed in the writing tasks of the textbook. Writing tasks belong involving factual knowledge were most dominant. In other words, the writing task of the textbook put more emphasis on LOTS rather than HOTS and they were not evenly distributed in every chapter. This indicated that the writing task in the textbook is not appropriate with achievements of junior high school English learning in the Merdeka curriculum. Therefore, the textbook needs to be evaluated to be consistent with the achievements of junior high school English learning in the Merdeka curriculum. Teachers can also modify learning or use other supporting textbooks which are consistent with the Merdeka curriculum.